2019
DOI: 10.1016/j.foodcont.2019.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Metataxonomic analysis of the bacterial diversity in table olive dressing components

Abstract: In this work, we have used a metataxonomic analysis to study the bacterial biodiversity in three types of commercial dressing and ingredients habitually used in table olive packaging. The bioinformatics analysis showed that salt samples (marine and spring) had the highest biodiversity indexes, followed by the aromatic herbs (thyme, oregano, and fennel) and finally by fermented dressing samples (garlic, pepper, and pepper paste). In salt samples, a significant high presence of Cytophagia, Sphingobacteria, Delta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…These authors reported the presence of OTUs at family/genera family/genera level in many cases below 100. On the contrary, in the study carried out on the seasoning material (salt, aromatic herbs, fermented garlic, or pepper) used during table olive packaging, a higher number of OTUs (> 3.000) were found 42 . This abundance could explain the intermediate values between fermented fruits and seasoning material found in this survey because, in olive packages, diverse types of seasoning material are added.…”
Section: Discussionmentioning
confidence: 81%
“…These authors reported the presence of OTUs at family/genera family/genera level in many cases below 100. On the contrary, in the study carried out on the seasoning material (salt, aromatic herbs, fermented garlic, or pepper) used during table olive packaging, a higher number of OTUs (> 3.000) were found 42 . This abundance could explain the intermediate values between fermented fruits and seasoning material found in this survey because, in olive packages, diverse types of seasoning material are added.…”
Section: Discussionmentioning
confidence: 81%
“…A previous study of the instability of fresh and traditional packed Aloreña de Málaga olives showed that their short shelf-life (<7 days for the fresh green elaboration) was caused by the activity of microorganisms present in the packed brine, which increased after the incorporation of seasoning material [ 6 ]. Previous studies through metagenomics and traditional approaches confirmed that the seasoning material is an important source of spoilage microorganisms [ 5 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, they are considered as a ready-to-eat product. However, the presence of residual sugars and the use of aromatic herbs (oregano, thyme, and fennel) and seasoning material (garlic and red pepper) in the packed product, which may involve a significant supply of microorganisms [ 5 ], make it a “living product”. This means that microbiological control is essential in order to ensure a stable and safe product.…”
Section: Introductionmentioning
confidence: 99%
“…Five samples (1,6,8,9, and 12) were recorded as acceptable or non-spoiled by the panelists (both producers and researchers). The combination of parameters on the spreadsheet (ratio of LAB/TAC, yeast count, and pH) gave the same result.…”
Section: Validationmentioning
confidence: 99%
“…The olive tree is an iconic species in Mediterranean cultural history and diet. Its multiple uses in the food industry (olive oil and table olives) and its omnipresence in many traditional agro-systems have made this species an economic pillar and cornerstone of Mediterranean agriculture [1]. Its role as a symbol of Italy, in particular of the Region of Apulia, has increased due to the emergence of the Xylella outbreak.…”
Section: Introductionmentioning
confidence: 99%